Optimizing Simple Learning Media to Increase Students' Interest in Learning at MI Salafiyah 2 Tasikmadu - Muhammad Abdullah; Vivi Nur Aisyah; Khusnul Khotimah; Misbahul Huda (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines the problem of low student learning interest in elementary classrooms and proposes the optimization of simple instructional media as a practical solution. The research aims to analyze how low-cost, easily constructed media can enhance student engagement and create meaningful learning experiences. A classroom action research design was implemented through iterative cycles involving planning, action, observation, and reflection. The findings indicate a consistent improvement in student learning interest, classroom participation, and emotional engagement after the integration of visual and concrete media. Simple media functioned not only as cognitive support but also as affective stimulation that reduced anxiety and increased motivation. The results demonstrate that effective learning innovation does not depend solely on advanced technology but on pedagogical creativity and reflective practice. The study concludes that optimizing simple media can serve as a sustainable instructional strategy, especially in schools with limited resources. This approach contributes to the development of practical, context-sensitive pedagogy and provides a replicable model for improving classroom interaction and student-centered learning.